Haloperidol for the treatment of delirium in ICU patients: a systematic review and meta‑analysis - Yue Zhao; Qing Wang; Biao Sun; Yanan Li; Chang Meng; Guobin Miao (European Journal of Medical Research)
Abstract Objectives Haloperidol is the most frequently prescribed medication for managing delirium in the intensive care unit (ICU). However, there is limited and inconclusive evidence regarding its efficacy. A meta-analysis was conducted by pooling data from recent clinical randomized controlled trials to assess the effectiveness of haloperidol in adult ICU patients with delirium. Methods Studies were searched in PubMed, Embase and Cochrane Library databases on August 10, 2024. We performed a meta-analysis to estimate the efficacy of haloperidol for the treatment of ICU adult patients with delirium. This study is registered with INPLASY, number 202480104. The estimates are expressed as odds ratio (OR) or mean difference (MD) with a 95% confidence interval (CI). Results A total of 2863 patients were included in the analyses. All the included studies were randomized controlled trials. The frequency of patients diagnosed with delirium used both confusion assessment method of intensive care unit (CAM-ICU) and intensive care delirium screening checklist (ICDSC) was 34% (n = 2863), and used CAM-ICU only was 66% (n = 2863). There was no difference in short-term (28–30 days) mortality between the two groups [OR = 0.89, 95% CI 0.60–1.32, P = 0.56] and long-term (90 days to 1 year) mortality [OR = 0.87, 95% CI 0.70–1.07, P = 0.19]. Furthermore, the haloperidol group demonstrated an advantage in reducing the length of ICU stay [MD = -1.13, 95% CI − 1.93–− 0.32, P < 0.05] compared to the placebo group, with no statistically significant difference in length of hospital stay [MD = − 0.24, 95% CI -1.71–1.24, P = 0.75]. Conclusions Haloperidol showed a significant trend in reducing the length of ICU stay. However, there was no statistical difference between the two groups in terms of delirium reduction.